Perspektif Filsafat tentang Dialektika Paradigmatik dalam Pendidikan - Ahmad Samawi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Philosophical Perspective on Dialectics Paradigm in Education. Education, which aims at changing learners' behaviors, is now confirmed with dialectics paradigm. Behavioristic thesis states that the changing of the behaviors is determined by factors external to the learners through environment condusive for them to develop. The anti-thesis, which is of constructivism, believes that the changing is merely caused by the internal factors of the learners, mainly related to their cognitive competence. As each of the two paradigms bears its own strengths and weaknesses, a new synthesis in education is needed, and dialectics paradigm, which is inspired by philosophical dialectics, seems to be the alternative.